PENGARUH AKTIVITAS MEMBACA TERHADAP PENGEMBANGAN KOSAKATA DALAM TEKS DESKRIPSI PADA KELAS IV SDN GROGOL II KECAMATAN GROGOL KOTA CILEGON - Ila Laela Sari; Nova Yanti; Desty Endrawati Subroto (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study was conducted at SDN Grogol II for fourth-grade students with the aim of evaluating the influence of reading activities on vocabulary development in descriptive texts, both individually and in groups, in relation to students' ability to write descriptive texts at the elementary education level. In addition, the research also examines how mastery of sentence structures affects descriptive writing skills and assesses the impact of the combination of vocabulary and sentence mastery on writing performance. A qualitative approach was employed, using the Think-Talk-Write (TTW) technique to enhance students’ descriptive writing skills. The study consisted of two cycles implemented through Classroom Action Research. Prior to the implementation of the TTW method, there were several obstacles in the learning process, particularly in the influence of reading activities on vocabulary development, which affected students’ ability to compose descriptive texts. At that time, only 21 students, or 52.5%, had a good understanding of the material, while 19 students, or 47.5%, still lacked sufficient comprehension. However, after applying the Think-Talk-Write (TTW) method, a significant improvement was observed, with 100% of the students achieving scores above 60.